Functionalised Nitrogen Heterocycles and the Search for New Antibacterials and Bioactives - Khan, Muhammad Kamran; Wang, Dandan; Moloney, Mark G. (Synthesis, 2020)
The importance of, and synthetic routes to, pyrrolidines and piperidines, along with their relevance to natural product synthesis and antibacterial drug discovery, are surveyed in the context of an extended programme of investigation from our own laboratories.1 Introduction2 Pyroglutamates2.1 Synthesised by Modification of an Existing Ring2.2 Synthesised by Construction of a New Ring3 Tetramates4 Metal Chelation5 Biological Activity6 Conclusion
Keywords: nitrogen heterocycles; antibacterials; bioactives; pyrrolidines; piperidines; natural products